2022
DOI: 10.1167/tvst.11.6.11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Foveal Development in Treatment-Naïve Extremely Preterm Infants

Abstract: Objective To characterize and quantify foveal development in treatment-naïve extremely preterm infants using optical coherence tomography. Methods In this cross-sectional study, eyes treated for retinopathy of prematurity before imaging were excluded. Inner retinal thickness and outer retina thickness at foveal center and foveal rim were assessed. Extremely preterm (EPT, <28 weeks gestational age) eyes were compared with infants more than 28 weeks of gestation using a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Our data are in line with the few existing studies investigating RNFL, such as the EPICure study that reported a thicker RNFL in A1 of the EDTRS grid in a group of 19-year-olds born extremely preterm compared to controls 6 . The results also coincide with findings of thicker central retinal layers with earlier gestational age in infants born extremely preterm 28 , 5 to -16-year-old children born preterm 29 . The centrifugal movement of inner retinal layers to the periphery and migration of outer photoreceptor layers towards the centre of the retina 30 occurs during late gestation and preterm birth therefore disrupt these processes 28 which can result in a thicker RNFL in the inner layers, as shown in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Our data are in line with the few existing studies investigating RNFL, such as the EPICure study that reported a thicker RNFL in A1 of the EDTRS grid in a group of 19-year-olds born extremely preterm compared to controls 6 . The results also coincide with findings of thicker central retinal layers with earlier gestational age in infants born extremely preterm 28 , 5 to -16-year-old children born preterm 29 . The centrifugal movement of inner retinal layers to the periphery and migration of outer photoreceptor layers towards the centre of the retina 30 occurs during late gestation and preterm birth therefore disrupt these processes 28 which can result in a thicker RNFL in the inner layers, as shown in this study.…”
Section: Discussionsupporting
confidence: 87%
“…It has been reported that compared to term born infant, premature infant or ROP infant eyes usually has shallower foveal pit, retain inner retinal layers at foveal center, thinner outer retinal layers, and indistinctive external limiting membrane band and ellipsoid zone (Figure 1) [32][33][34].…”
Section: Immature Retinal and Choroidal Morphologymentioning
confidence: 99%